LAND SUBSIDENCE INDUCED BY THE OVEREXPLOITATION OF THE AQUIFERS IN KALOCHORI VILLAGE – NEW APPROACH BY MEANS OF THE COMPUTATIONAL GEOTECHNICAL ENGINEERING - Loupasakis, C.; Rozos, D. (Bulletin of the Geological Society of Greece, 2010)
Land subsidence induced by the overexploitation of the aquifers in Kalochori village has been occurring since 1965. The excessive water pumping led to the development of surface subsidence reaching, in several areas, the maximum values of 3 to 4m. The evaluation of the geological, geotechnical and hydrogeological setting of the wider Kalochori region as well as the historical background of the subsidence phenomena provided variable data, which were finally used for the study of the phenomenon by means of a finite element method simulation. The availability of the various geodetic records allowed the cross-checking of the results and the conduction of all necessary back analyses. Also, the knowledge of the land use distribution and the activities taking place in the wider Kalochori region helped the rational interpretation of the phenomenon and the detection of its causal factors.